Subjective Well Being Of Employees: A Key Indicator in Creating a Healthy and Productive Work Environment - Rahmad; Daharnis; Ardi, Zadrian (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
Employees in this era are expected not only to complete tasks efficiently, but also to adapt, collaborate, and manage increasing stress. Employees with high subjective well-being tend to show better performance, high loyalty to the company, and better ability to cope with work pressure. This study aims to explore the level of employee Subjective Well-Being as a key indicator in creating a healthy and productive work environment. The research method uses a descriptive quantitative research type with data collected from 31 Viera employee respondents, this study analyzes employee perceptions of their working conditions, which are grouped into four categories: "Very Good", "Good", "Less Good", and "Not Good". The results of the analysis show that most employees are in the "Less Good" category (54.8%), followed by the "Good" category (32.2%), while only 3.2% feel their working conditions are very good and 9.6% feel very dissatisfied. These findings indicate that most employees are not satisfied with their working conditions, which has the potential to affect their subjective well-being.